The Role and Function of Fatty Acids in Feed on Fish Growth - Prananda, Muhammad Rizky; Adriani, Yuli; Pratiwy, Fittrie Meyllianawaty; Iskandar, Iskandar; Haetami, Kiki; Zidni, Irfan; Herman, Roffi Grandiosa (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
Essential fatty acids play a crucial role in fish growth and health. A quality feed containing the right amount of fats can promote fish growth and support metabolic functions. Fatty acid requirements vary depending on the fish species and habitat, with freshwater fish tending to require more n-6 fatty acids, while marine fish require more n-3 fatty acids. The use of fat in feed should be well regulated, as too high levels can interfere with the digestive and metabolic processes of the fish. The use of fish oil mixed in feed as much as 1.5% can help improve the growth performance of carp. Magot oil mixed into the feed as much as 15%/100 g gives the best growth performance in carp. Soybean oil used as much as 10% in feed can increase the content of omega 3, EPA, and DHA in catfish meat. Coconut oil used in feed at 6% proved to have a good impact on the DHA content of tilapia. The purpose of this paper is to review the literature on the role and function of fatty acids in fish growth.